2018
DOI: 10.1097/01.aog.0000533490.61961.5f
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Surgical Outcomes During Peripartum Hysterectomy [26J]

Abstract: INTRODUCTION: Peripartum hysterectomy (PH) is a lifesaving procedure known to have increased morbidity and mortality over elective hysterectomy. Non-white surgical patients frequently have poorer outcomes than white patients undergoing the same procedure. We sought to analyze patients undergoing PH and compare intraoperative and postoperative outcomes by race. METHODS: We performed a retrospective analysis of female patients (age 12–55) who underwent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A 2006 study found that Aboriginal women in Western Australia were more likely than non-Indigenous women to be given hysterectomy for the treatment of mild gynaecological disorders, particularly in rural areas (Spilsbury et al 2006). Peripartum hysterectomy (a high-risk surgery conducted immediately after childbirth) increased between 2010 and 2016 in the US and was more likely to be performed on Black women, with complications resulting from it more frequently in Black-Hispanic-and Asian-American women than in White women (Martin et al 2018;Ryan et al 2018). Racial-minority women of all kinds in the US have also been identified as less likely than White women to receive minimally invasive gynaecological procedures (Ranjit et al 2017).…”
Section: Clinical Rationales For Hysterectomy In Indiamentioning
confidence: 99%
“…A 2006 study found that Aboriginal women in Western Australia were more likely than non-Indigenous women to be given hysterectomy for the treatment of mild gynaecological disorders, particularly in rural areas (Spilsbury et al 2006). Peripartum hysterectomy (a high-risk surgery conducted immediately after childbirth) increased between 2010 and 2016 in the US and was more likely to be performed on Black women, with complications resulting from it more frequently in Black-Hispanic-and Asian-American women than in White women (Martin et al 2018;Ryan et al 2018). Racial-minority women of all kinds in the US have also been identified as less likely than White women to receive minimally invasive gynaecological procedures (Ranjit et al 2017).…”
Section: Clinical Rationales For Hysterectomy In Indiamentioning
confidence: 99%